Praktik Jual Beli Tumpukan (Jizaf) dalam Mewujudkan Konsep Keadilan Bisnis Islam - Sumarni Sumarni; Saiful Mukhlis; Wahid Haddade (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to understand the practice of buying and selling the stack system (Jizaf) in realizing the concept of Islamic business justice for fish traders in Lonrae Auctions, Bone Regency. This study uses qualitative research with phenomenological, sociological and Shari'a approaches. The data sources for this study come from primary data, namely: 1 fish trader (juragan)and 4 fishermen and secondary data comes from various sources, namely books, journals and other research. Furthermore, the data collection method used by observing, interviewing and documentation. Data analysis in this study went through three stages, namely data reduction, data presentation and drawing conclusions. In this data analysis using the concept of buying and selling Jizaf as data analysis. The results showed that the practice of buying and selling piles (Jizaf) in realizing the concept of Islamic business justice that occurred at the Lonrae Fish Auction in Bone Regency, from the point of view of the pillars of buying and selling jizaf (contracts and people who are in akad) has met the requirements justified in the Muamalah Fiqh rules . However, judging from the aspect of the validity of the contract object being traded, it still creates tadlis and gharar in the buying and selling transaction process. With the elements of usury, tadlis (fraud) and gharar (obscurity) in buying and selling transactions, this is not in accordance with the concept of realizing justice in business because of injustice in buying and selling.